Peningkatan Pengetahuan Guru IPA dan Biologi tentang Metode Pembelajaran Case method terintegrasi Pandemi COVID-19 - Yosi Laila Rahmi; Elsa Yuniarti; Rahmawati Darussyamsu; Rahmadhani Fitri (Universitas Indraprasta PGRI, 2022)
The purpose of this activity is to provide scientific information and knowledge concerning to the update of the immune system topic which is closely related to COVID-19. This activity provides health information toward science and biology teachers regarding efforts to maintain immunity during the COVID-19 pandemic. Teachers need to develop the learning process, so that teachers are able to present learning that is innovative, interactive, interesting, meaningful, and fun. The approachment taken by providing training in the case method learning, case method provides stimulation to teachers on how to create development in the learning process. This activity took place in Aka Barayun, Harau, Lima Puluh Kota regency. This activity was attended by 50 teachers of Science and Biology Lima Puluh Kota regency. Most of the teacher's agree with the implementation of the case method as an innovative learning method integrated with the COVID-19 pandemic phenomenon. This case method training can increase teacher knowledge in developing learning method. Based on the results of the pre-test questionnaire given to teachers before the training began, 64% of teachers did not know the case method learning. Most of teacher 57% strongly agree and the rest of the teacher 43% agree to integrate cases in the learning process as the starting point of the learning process.